Big Data Analytics Competence and Transformational Leadership in Managerial Self-Efficacy for Data-Driven Decisions - Muhammad Daan Agung Lazuardi; Umi Muawwanah; Bhakti Hendrakusuma (LPPM STIE KRAKATAU, 2026)
The rapid digital transformation within the energy sector has increased organizational dependence on data-driven decision-making, where managerial effectiveness is shaped not only by technological capability but also by psychological readiness and leadership support. This study examines the influence of big data analytics competence and transformational leadership on managerial self-efficacy in data-driven decision-making. A quantitative explanatory design was applied, involving 72 managerial employees selected through total sampling. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using multiple linear regression in SPSS version 26. The results show that big data analytics competence has a positive and significant effect on managerial self-efficacy (β=0.221; p=0.003), whereas transformational leadership has a stronger positive influence (β=0.682; p<0.001). Simultaneously, both variables significantly explained managerial self-efficacy (R²=0.681; F=72.541; p<0.001). The study concludes that both factors enhance managerial self-efficacy, with transformational leadership being the more dominant factor. However, this study is limited by its single-organization context and cross-sectional design. Theoretically, this study integrates the Resource-Based View and Social Cognitive Theory, while practically, it emphasizes the need to strengthen analytical competence and transformational leadership to improve data-driven decision-making.